Establishing the gap between Practicing and Teaching Accounting. - , Dr. Joshua W. Chesoli (IJRDO - Journal of Business Management, 2019)
This article is about the things that those teaching Accounting in academic institutions should emphasize on in order to produce graduates who are ready for the job market. The content of most accounting programmes taught in schools and colleges does not empower the students with knowledge of the real situations that they will face when they practice Accounting. This paper is based on a study carried out in various academic institutions and on another study carried out among those practicing Accounting. The study found out that Accounting educators emphasis a lot about using sophisticated techniques to solve situations, which in many cases are irrelevant to those practicing Accounting. It was also found out that Accounting education places less emphasis on computerized accounting systems even though most companies are using Computerized Accounting systems to manage their accounts. It is recommended that Accounting Educators should teach more about performance management and strategic management. Also, computerized Accounting training should be incorporated into the curricula of Accounting Programs in tertiary institutions to prepare students for the job market since knowledge in such systems is required in the job market. In addition, the educators and researchers from various disciplines should collaborate with those practicing and conducting research on how to improve what is taught.